A new species of Echeandia (Asparagaceae) from Jalisco and a key to the Mexican species with white tepals and connate anthers - Rodríguez, Aarón; Ortiz-Brunel, Juan Pablo; Rivas-Salazar, Pedro Daniel (Phytotaxa, 2026)
Echeandia bracteosa is described with specimens from the municipality of Pihuamo, Jalisco, in western Mexico. The plants of the new species develop root-thickenings near by the corm. They grow 2–9 basal, linear-lanceolate leaves and a glabrous peduncle with 8–12 scarious bracts along it and below the first branch of the panicle. The flowers are inclinate with white tepals; the filaments are filiform, muricate, and contorted; and the anthers connate in a cone and with apical pores. Morphologically, E. bracteosa resembles E. parviflora. Both species have white tepals; filiform, muricate, and contorted filaments; and connate and poricidal anthers with anthesis occurring at down. However, E. bracteosa has glabrous peduncle and straight and ascendent leaves while the peduncles of E. parviflora are scabrellous toward the base and the leaves are falcate or incurved. In E. bracteosa, the anthers connate in a cone, whereas in E. parviflora these form a cylinder. In E. bracteosa, the capsules are cylindric as opposed to globose in E. parviflora. Echeandia bracteosa grows on calcareous rocks and crevices among them in tropical dry forest. In contrast, E. parviflora prefers soils derived from volcanic rocks. Color photographs, distribution maps, and a key for the species with white tepals and connate anthers in Mexico are included.